Disclosure to friends or family and consequences after interpersonal violence: intersections of sexual identity and race. Issue 5 (22nd June 2022) - Mennicke, Annelise; Bowling, Jessamyn; Geiger, Elizabeth; Brewster, Melanie
Abstract: Objective: This study's purpose was to examine whether disclosures to friends or family post-victimization was associated with emotional and academic consequences (e.g. feeling detached from others, getting worse grades) among students grouped by sexual identity and race intersections. Participants and Methods: We analyzed data from an online survey that was distributed to students ( n  = 6, 331) at a university in the Southeast. Results: Path analyses indicated disclosure to friends and family partially mediated the relationship between victimization and consequences, such that an increase in the number of disclosures was associated with an increase in the number of consequences. These paths were significant among White sexual minority victims, sexual minority victims of color, White heterosexual students, and heterosexual students of color. Conclusions: These findings indicate that disclosure to informal sources is associated with amplified consequences, which may be ameliorated by training friends and family to respond to disclosures in a supportive manner.